2014
DOI: 10.1080/15287394.2013.876696
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Activities and Expression of Antioxidant Enzymes in Wistar Rats Exposed for 90 Days to a Modified Clay

Abstract: Although clays are wildly used in a range of applications, the toxicity assessment of these new materials is still scarce. In the present study, oxidative stress induced by Clay 1, a novel clay, was determined in rats after 90 d of oral exposure. The activities of antioxidant enzymes, namely, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione S-transferase (GST), were examined. In addition, genetic expressions of SOD and CAT and relative protein abundance of CAT were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Regarding oxidative stress biomarkers, Kibanova et al (2009) reported that nontronites induced higher LPO than hectorite in brain supernatant solutions exposed to up to 1000 ppm. Maisanaba et al (2014e), however, did not find any alteration in the LPO, SOD, GPx and GST activities in the liver and kidney of rats exposed for 90 days to a 40 mg/kg bw/d Mt-modified clay (Clay1), although the CAT activity, gene expression and protein abundance were increased in the kidney. In relation to genotoxicity, EFSA (2013) referred to a study in which no chromosomal aberrations were detected in rats exposed to bentonite through diet for 15 days.…”
Section: In Vivo Toxicological Assaysmentioning
confidence: 73%
“…Regarding oxidative stress biomarkers, Kibanova et al (2009) reported that nontronites induced higher LPO than hectorite in brain supernatant solutions exposed to up to 1000 ppm. Maisanaba et al (2014e), however, did not find any alteration in the LPO, SOD, GPx and GST activities in the liver and kidney of rats exposed for 90 days to a 40 mg/kg bw/d Mt-modified clay (Clay1), although the CAT activity, gene expression and protein abundance were increased in the kidney. In relation to genotoxicity, EFSA (2013) referred to a study in which no chromosomal aberrations were detected in rats exposed to bentonite through diet for 15 days.…”
Section: In Vivo Toxicological Assaysmentioning
confidence: 73%
“…To evaluate the harm to cells by inhalable mineral granules which constitute the bulk of the granules, are important factors that should not be ignored. Scientifically objective evaluation of the components of inhalable mineral granules that pose a danger to cells could provide the basis for developing standards to detect and reduce it in the environment (Zhang et al, 2005;Sellamuthu et al, 2011;Maisanaba et al, 2014 …”
Section: Introductionmentioning
confidence: 99%
“…oxidative stress level (Kryuchkova et al, 2016). Regarding a study conducted by Maisanaba et al (2014) on the effect of clay mineral nanoparticles on antioxidant enzymes of male Wistar rats with 40 mg/kg/day oral exposure, it was reported that clay nanoparticles had no effect on the levels of MDA in the liver and kidneys. As a result, these nanoparticles did not play a role in changing levels of oxidative stress (Maisanaba et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding a study conducted by Maisanaba et al (2014) on the effect of clay mineral nanoparticles on antioxidant enzymes of male Wistar rats with 40 mg/kg/day oral exposure, it was reported that clay nanoparticles had no effect on the levels of MDA in the liver and kidneys. As a result, these nanoparticles did not play a role in changing levels of oxidative stress (Maisanaba et al, 2014). In another similar study by Shi et al (2006), it was found that oral exposure to montmorillonite nanocomposite had no effect on the levels of superoxide dismutase, glutathione peroxidase, and MDA parameters of the liver and blood serum of broiler chickens (Shi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%